A Study on Students' Satisfaction with Classroom Teaching of Independent Adult Universities Based on SERVQUAL and IPA Models, Taking Beijing Haidian Adult University as an Example. (21st January 2022) - Wang, Xiaoya; Gao, Yuanyang; Li, Sumei
Abstract : To some extent, students' satisfaction with classroom teaching reflects the teaching quality of the school. In view of the characteristics of independent adult universities in recent years, which are characterized by great age difference, uneven foundation, and diversified demands, it is necessary to start the research from the perspective of students, through sufficient investigation, forming a survey index, setting up questionnaires, and conducting empirical research on their satisfaction with classroom teaching. In the study, the service quality gap model (SERVQUAL) is introduced; the importance-satisfaction model, importance-performance analysis (IPA), was used to check the consistency of the SERVQUAL research results; the current status of satisfaction was obtained; and countermeasures and suggestions were proposed to improve students' satisfaction with classroom teaching of independent adult universities.